Soluções do tipo vórtice em um modelo de Maxwell-Chern-Simons-Higgs com campos de Gauge distintos - Guimarães, Thiago Vinícius Moreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this dissertation we mean to seek vortex solutions in a model not found in literature, consisting in Lagrangian density given by a Maxwell term generated by a field gauge A mu,and Chern-Simons term generated by another field gauge Aµ, using a self-dual potential with nontrivial sixth-order vacuum. This model features an interesting first order equation for Ø, with solution exact, but it is not consistent with the second order equation, and therefore invalid. Moreover, it was not possible to minimize the model's energy, since the contribution of the electric field can not be eliminated without causing inconsistencies in the equations of motion. To try work around this problem, we tried to introduce a new mixed Chern-Simons term, composed of two fields Aµ and Aµ. In this context the energy was minimized without causing problems the equations of motion, but has not yet been possible to obtain vortex solutions, because the solutions to Ø diverges. Again, without the vortex solutions, the original model has changed, to contain a real scalar field N. Thus, the energy of the system was minimized and topological vortex solutions were found. Yet, we developed an idiosyncratic approach to the Bogomol'nyi's mechanism without the direct need to complete square and naturally based on the consistency between the self-duals equations and equations of motion

Nessa dissertação temos o intuito de buscar soluções do tipo vórtice em um modelo não encontrado na literatura, que consiste em um densidade de lagrangiana formada por um termo de Maxwell gerado por um campo de gauge Aµ e um termo de Chern-Simons gerado por outro campo de gauge Aµ, fazendo uso de um potencial autodual com vácuo não trivial de sexta ordem. Tal modelo apresenta uma interessante equação de primeira ordem nas derivadas para Ø, com solução exata, porém ela não é consistente com a equação de segunda ordem, sendo portanto invalida. Além disso não foi possível minimizar a energia do sistema, pois a contribuição do campo elétrico não pode ser eliminada sem causar inconsistências nas equações de movimento. Para tentar contornar esse problema, foi tentado introduzir um novo termo de Chern-Simons, misto, composto pelos dois campos Aµ e Aµ. Nesse contexto a energia pôde ser minimizada sem causar problemas às equações de movimento, porem ainda não foi possível obter soluções do tipo vórtice, pois as soluções para Ø encontradas divergiam. Novamente sem soluções do tipo vórtice, o modelo original foi alterado, de forma a conter um campo escalar real N e um potencial também de sexta ordem. Com isso, a energia do sistema foi minimizada e soluções topológicas do tipo vórtice foram encontradas. Ainda desenvolvemos uma forma idiossincrática de abordar o mecanismo de Bogomol'nyi sem a necessidade direta de completar quadrado e se baseando naturalmente na consistência entre as equações autoduais e as de movimento.
Kind of vortex solutions in a model of Maxwell-Chern-Simons-Higgs with different Gauge fields
Keywords: Maxwell, Equações de; Campos de calibre (Física); Taylor, Vórtices de; Gauge fields (Physics)